The duke's Christmas bride - Bradley, Anna (Romance fiction writer) (Bradley, Anna (Romance fiction writer). Drop dead dukes., 2024)
"Alarmed by the sound of an intruder, Rose St. Claire fetches her pistol. She's shocked to discover that the trespasser is a handsome gentleman--one who states that the house, which Rose recently inherited from her late benefactor, was stolen from his father decades ago. He claims it is now his. And it is--but not entirely. As it turns out, Hammond Court has been left to them both--and neither can evict the other without forfeiting their right to the property...Wealthy and ruthless, Maxwell Burke, Duke of Grantham, has spent years regaining the many properties his father lost to bad wagers. Only Hammond Court remains. But Rose has no intention of leaving. In fact, as Christmas draws near, circumstances force Max to plan a holiday party, and Rose is all too happy to help. Max despises such merriment--until he sees it as an opportunity...Max will forgive the debt of another young duke's family if the attractive gentleman woos Rose at the party, ultimately marries her--and returns her share of the estate to Max. It's foolproof. Except that Rose's spirited joy is seductive, recalling within Max long ago feelings of happiness--and awakening a deep attraction. Has Max cooked his own Christmas goose--or is there a chance love will prevail?..."--